Bucket of nails: foreign body ingestion in a young adult - Da Jun Than; Chen, Jonathan Ken Seak; Mohammad Firdaus Bolong @ Mohd Darwis; Mohd Firdaus Mohd Hayati (John Wiley & Sons, 2022)
Foreign body (FB) ingestion is a potentially serious health problem. Majority of the cases are seen in pediatric populations; when encountered in adults, they are usually due to underlying mental health disturbances, edentulous state or alcohol intoxication. Most ingested FBs pass spontaneously. However, 10%–20% of cases require endoscopic intervention, while 1% or less require surgical procedures due to complications such as bowel perforation or obstruction. Medical history obtained from the patient is highly critical in the diagnosis of FB ingestion. Patients can present with a wide array of symptoms and signs such as dysphagia, non-specific abdominal pain, atypical chest pain, choking, gastrointestinal (GI) obstruction, GI bleeding as well as GI perforation. Presentations, clinical findings and management are distinct and based on the anatomical region where the FB is located.